Workforce suicide: barriers and postvention in the healthcare sector - Luce, Ann (CRC focus, 2025)
"In 2019, National Health Service Trust in England lost 11 members of current and former staff members to suspected suicide. Set against the backdrop of the COVID-19 Pandemic, this book is a case study of how one workplace was affected. It offers a critical examination of how management responded, reflecting on their missteps, their desire to learn, their uncertainty about what actions to take or where to begin, and how they ultimately relied on staff guidance to chart a path forward. Based on research conducted in 2021, this book presents a series of recommendations outlining how to integrate suicide prevention and postvention into organizational policies and wellbeing strategies. The book includes a "Seeking Support Framework", "Postvention Communication Strategy Model" and a "Healthcare Workforce Postvention Toolkit", which are practical tools that readers can embed in their own workplaces quicky and efficiently to prevent suicide. This book reveals to the reader how anti-suicide measures can be put in place in a healthcare setting or any organization. Workforce Suicide: Barriers and Postvention in the Healthcare Sector is a sobering yet vital read for any student, researcher or practitioner in the fields of occupational health and safety, healthcare and healthcare management, nursing, medicine, social care or occupational therapy"-- Provided by publisher